Substituted 3-R-2,8-Dioxo-7,8-dihydro-2H-pyrrolo[1,2-a][1,2,4] triazino [2,3-c]quinazoline-5a(6H)carboxylic Acids and their Salts-a Promising Class of Anti-inflammatory Agents - Stavytskyi, V. V.; Antypenko, O. M.; Nosulenko, I. S.; Berest, G. G.; Voskoboinik, O. Yu.; Kovalenko, S. I.; Ставицький, Віктор Валерійович; Антипенко, Олексій Миколайович; Носуленко, Інна Степанівна; Берест, Галина Григорівна; Воскобойнік, Олексій Юрійович; Коваленко, Сергій Іванович (Sharjah : Bentham Science Publishers, 2021)
Abstract: Background: Fragment-based drug design as well as in silico pre-screening of affinity to biological targets are among the most effective methods of medicinal chemistry. Abovementioned approaches were used for purposeful search of anti-inflammatory agents among quinazoline condensed derivatives. Objective: Purposeful synthesis of novel 3-R-2,8-dioxo-7,8-dihydro-2H-pyrrolo[1,2-a][1,2,4]triazino[2,3-c]quinazoline-5a(6H)carboxylic acids and their salts as promising anti-inflammatory agents, evaluation of their structure by physicochemical methods and establishing of their anti-inflammatory activity. Method: The structures of target compounds were proposed due to principles of fragment-based drug design. The features of the synthesized compounds structures were evaluated by IR-, NMR spectroscopy and chromatography-mass spectrometry and were discussed in detail. Probable molecular mechanisms of activity were predicted due to molecular docking. The anti-inflammatory activity was determined by their ability to reduce the formalin- and carrageenan-induced paw edema in rats.
Keywords: anti-inflammatory activity; drug design; 3-(2-aminophenyl)-6-R-1,2,4-triazin-5(2H)ones; pyrrolo[1,2-a][1,2,4]triazino[2,3-c]quinazolines; molecular docking; SAR